Preparation and electromagnetic wave absorption properties of PDC–SiC/Si3N4 composites using selective laser sintering and infiltration technology - Siwen Yu; Tao Zeng; Jue Zhao; Honghao Jiang; Zuzheng Chen; Yipeng Yang; Zhiqiang Zhong; Su Cheng (Journal of Materials Research and Technology, 2023)
Polymer-derived silicon carbide/silicon nitride (PDC–SiC/Si3N4) composites were prepared by additive manufacturing and infiltration technology. The composite green bodies were prepared using selective laser sintering (SLS) three-dimensional (3D) printing technology. Carbon-rich PDC–SiC was generated via precursor infiltration and pyrolysis (PIP) to increase the dielectric constant and enhance the electromagnetic wave (EMW) attenuation ability of the composites. Low-dielectric materials, including Al2O3, TiO2, and AlPO4, were introduced by sol infiltration to improve the impedance-matching characteristics of the composites. The results showed that the EMW absorption ability of the PDC–SiC/Si3N4 composites enhanced after two and four PIP cycles, whereas it degraded with further increasing the PIP cycle number. Among all the samples, the PDC–SiC/Si3N4 composite after four PIP cycles displayed an excellent EMW absorption ability with the minimal reflection loss of −46.79 dB, whereas its effective absorption bandwidth was narrow. Comparing to the sample without infiltration, the effective absorption bandwidth of the samples after the infiltration treatment with TiO2 or Al(H2PO4)3 sol increased from 1.44 GHz to 4.08 GHz and 3.52 GHz, respectively. These results demonstrate that the PIP process and infiltration with TiO2 or Al(H2PO4)3 sol resulted in a 3D-printed PDC–SiC/Si3N4 ceramic that is a promising EMW absorption material suitable for high-temperature environments.